Directly labeled DNA probes using fluorescent nucleotides with different length linkers. - Zhu, Z (1994)
Directly labeled fluorescent DNA probes have been made by nick translation and PCR using dUTP attached to the fluorescent label, Cy3, with different length linkers. With preparation of probes by PCR we find that linker length affects the efficiency of incorporation of Cy3-dUTP, the yield of labeled probe, and the signal intensity of labeled probes hybridized to chromosome target sequences. For nick translation and PCR, both the level of incorporation and the hybridization fluorescence signal increased in parallel when the length of the linker arm is increased. Under optimal conditions, PCR yielded more densely labeled probes, however, the yield of PCR labeled probe decreased with greater linear density of labeling. By using a Cy3-modified dUTP with the longest linker under optimal conditions it was possible to label up to 28% of the possible substitution sites on the target DNA with reasonable yield by PCR and 18% by nick translation. A mechanism involving steric interactions between the polymerase, cyanine-labeled sites on template and extending chains and the modified dUTP substrate is proposed to explain the inverse correlation between the labeling efficiency and the yield of DNA probe synthesis by PCR.